Research Universities in Developing and Middle-Income Countries - MacGregor, Karen (International Higher Education, 2014)
Research universities in low and middle-income countries have crucial roles to play in developing differentiated and effective academic systems and in making it possible for their countries to join the global knowledge society and compete in sophisticated knowledge economies.